Complications in Aneurysmal Subarachnoid Hemorrhage Patients With and Without Subdural Electrode Strip for Electrocorticography. Issue 3 (June 2016) - Drenckhahn, Christoph; Windler, Claudia; Major, Sebastian; Kang, Eun-Jeung; Scheel, Michael; Vajkoczy, Peter; Hartings, Jed A.; Woitzik, Johannes; Dreier, Jens P.
Abstract : Purpose: Patients with aneurysmal subarachnoid hemorrhage (aSAH) frequently develop secondary noninfectious and infectious complications with an important impact on clinical course and outcome. In this study, we report on the rate of typical extracranial and intracranial complications in 30 prospectively enrolled patients with severe aSAH who received a linear subdural recording strip for continuous electrocorticography to detect ictal epileptiform events and spreading depolarizations. Methods: The group was compared with 30 retrospectively included patients with aSAH who had not received a subdural recording strip, but were treated during the same period. The control group was matched according to an aSAH grading system, sex, and establishment of external ventricular drainage, but could not be matched according to aneurysm treatment and focal brain lesions such as initial intracerebral hemorrhages. Results: No evidence was found that procedures of the electrocorticography study led to clinically relevant complications. In particular, the subdural strip did not lead to local damage of brain tissue or any increased rate of meningitis/ventriculitis. The median score on the modified Rankin Scale on day 15 was the same in both groups. Minor differences between both groups are explained by the limitations in the study design. Conclusions: Our study suggests that neuromonitoring with a subdural recording strip for up to 15 days can be safely performed in patients with aSAH.